(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The present study was undertaken to assess the impact of emotional intelligence and perspective taking upon managerial effectiveness. A sample of 300 middle level managers of MNCs from NCR (National Capital Region) was collected. Emotional Intelligence Scale by Uma Devi L., Perspective Taking Scale by Jean Brittain Leslie et. al., and Managerial Effectiveness Scale developed by Dr. Upendra Dhar were used as measures to collect sample data. Data collected was subjected to SPSS and Mean, SDs and 2way ANOVA was calculated. The results show that both emotional intelligence and perspective taking have significant impact upon managerial effectiveness. Thus the hypothesis that emotional intelligence and perspective taking together significantly affect managerial effectiveness stands accepted and the null hypothesis gets rejected.